Farmer's handbook on introduced and local banana cultivars in the Philippines - Cruz, F.S. de la; Gueco, L.S.; Damasco, O.P.; Huelgas, V.C.; Cueva, F.M. de la; Dizon, T.O.; Sison, M.L.J.; Banasihan, I.G.; Sinohin, V.G.O.; Molina, Jr., A.B. (2008)
This manual provides information on the morphological and agronomic traits, fruit characteristics, reactions to common diseases, and uses of 21 introduced and 8 local cultivars based on field trials carried out through the Bioversity-DA-BAR-NRMDC programme. It is intended to serve as a useful guide in the identification and selection of cultivars for further evaluation by researchers and planting by interested banana growers.